Pengaruh besar arus pengelasan dan kecepatan volume alir gas pada proses las GMAW terhadap ketangguhan aluminium 5083 - I N Budiarsa (Jurnal Energi Dan Manufaktur, 2008)
Level of welding current and flow rate of gas volume are welding parameters, which can influence result of welding process use of GMAW (Gas Metal Arc Welding) at material of Aluminium 5083. Testing to be carried out is impact test with nocth type of standart test from A.S.T.M. standart pt.31 Designation E23-82. Specimens to be applied use of standard from DIN 50115 and standart ISO V nocth. Treatments to be given to specimen are variation flow rate of gas volume and level of welding current. By using of factorial experiment method can be showed that level of welding current and flow rate of gas volume and its interaction give a significance effect toward toughness properties of material. The result obtained with level of welding current 250 Ampere at variation of gas volume flow rate (17 l/minute, 18 l/minute, 19l/minute) gives result low level toughness properties of material. The lowest level toughness (26,967) at (250 Ampere, 19l/minute)